Alteplase vs. Tenecteplase: An In-depth Analysis of Their Relative Effectiveness in Treating Acute Ischemic Stroke - Azhar, Muhammad Junaid; Butt, Ayesha Imran (Journal of the Pakistan Medical Association, 2024)
Dear Editor, Stroke stands as the second-leading cause of death worldwide [1, 2]. Each year, over 12 million individuals are impacted by stroke, resulting in approximately 6.5 million fatalities [1]. Stroke globally ranks as the third-leading factor causing a combination of death and disability [2]. Every year, around seven hundred thousand individuals in the United States undergo an Acute Ischemic Stroke (AIS), making up 85% of all stroke cases [2]. New treatments like intravenous thrombolysis and mechanical thrombectomy have cut mortality by 10% compared to older methods, enhancing long-term disability prevention rates following Acute Ischemic Stroke [2]. Alteplase is the sole FDA-approved thrombolytic drug in AIS within the first 4.5 hours. Despite its potential for disability-free recovery, its usage is constrained by a brief time window and adverse effects, notably a 6% risk of symptomatic bleeding. In addition, its fibrinolytic efficacy is limited, achieving vascular reopening in less than half of the patients, and can cause cytotoxicity to the already hypoxic brain with resultant cerebral edema [2]. Tenecteplase (TNK), a modified variant of alteplase, has improved features including greater fibrin selectivity and longer half-life and is given as a single bolus instead of an infusion, thanks to genetic recombinant technology [3]. Numerous studies have supported TNK’s efficacy over alteplase in treating AIS. In 2016, Bruce C.V. Campbell and colleagues demonstrated that, according to the analysis of modified Rankin scale scores, tenecteplase exhibited a more favorable overall functional outcome compared to alteplase [4]. A dosage of 0.25 mg/kg of tenecteplase emerges as a promising alternative to replace alteplase as the preferred treatment for patients with AIS occurring within 4.5 hours due to TNK’s superior early neurological recovery rates and comparable safety outcomes [3]. Despite gathering evidence from experimental trials indicating TNK’s advantages over alteplase for AIS, the use of TNK at a dosage of 0.4 mg/kg appears to pose safety concerns when compared to alteplase [3]. Bruce C.V. Campbell and his fellow researchers revealed in their study that in spite of the beneficial effects of TNK relative to alteplase, there was no significant variation in the speed of recovery to independent function. Notably, they found no discernible distinction in the occurrence of intracranial hemorrhage [4]. —Continue